The Correlation between Body Mass Index, Physical Activity and Blood Pressure with Quality of Life in Elderly Hypertension - Andi Astillawati; Edi Purwanto; Lukman Nulhakim (PT FORMOSA CENDEKIA GLOBAL, 2023)
Hypertension is a global and national health problem known as the silent killer,